Clinical evaluation of reading performance in refractive lens exchange with a diffractive continuous-range-of-vision intraocular lens - Baur, Isabella; Auffarth, Gerd U.; Łabuz, Grzegorz; Stengele, Annette; Hallak, Mustafa; Khoramnia, Ramin (American journal of ophthalmology, 2023)
Purpose - Evaluation of reading performance with a novel presbyopia correcting intraocular lens (IOL) in refractive lens exchange using an electronic reading desk. - Design - Prospective interventional before-and-after clinical study. - Methods - In total, 56 eyes of 28 patients were included. Bilateral implantation of the TECNIS Synergy IOL (Johnson & Johnson Surgical Vision) during a bilateral delayed sequential refractive lens exchange procedure. Uncorrected and distance corrected reading acuity, reading distance, reading speed, and the smallest print size that could be read effectively at a set (40 cm/80 cm) and subjectively chosen near and intermediate distance were assessed using the Salzburg Reading Desk preoperatively and 6 months after surgery. - Results - Uncorrected near reading acuity increased from 0.61 ± 0.16 logarithm of the minimum angle of resolution (logMAR) preoperatively to 0.05 ± 0.09 logMAR postoperatively at the set near distance (40 cm) and from 0.60 ± 0.11 logMAR to 0.07 ± 0.08 logMAR at the subjectively preferred distance (39.6 ± 5.3 cm and 37.7 ± 4.3 cm). Uncorrected intermediate reading acuity was 0.39 ± 0.19 logMAR preoperatively and 0.08 ± 0.07 logMAR postoperatively at the set intermediate distance (80 cm) and 0.43 ± 0.21 logMAR preoperatively and 0.07 ± 0.08 logMAR postoperatively at the preferred intermediate distance (73.5 ± 9.5 cm and 73.3 ± 5.9 cm). - Conclusions - Uncorrected intermediate and near reading function considerably improved after bilateral implantation of the TECNIS Synergy IOL. Patients preferred a closer near and intermediate distance to the set distances. However, reading function was comparable for the set and subjectively preferred distances.
Online verfügbar 18 Januar 2023, Artikelversion 28 Februar 2023
Gesehen am 24.03.2023